PENGARUH LATIHAN DRILL TERHADAP PENINGKATAN TEKNIK DASAR SHORT PASSING SEPAK BOLA DI SMP NEGERI 11 KOTA PONTIANAK - Putra, Iswahyudi; Suriatna, Eka; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVarious efforts to improve student soccer skills have become a special concern in every school. This is due to the many problems faced in the process of fostering soccer skills, particularly in the extracurricular of SMP Negeri 11 in Pontianak. One of the skills that have not been mastered by most extracurricular students is short passing by using the inner-foot. As a result, many did short passing incorrectly since they did not know the right model. This is an experimental study on the soccer extracurricular students of SMPN 11 Pontianak. The drilling method was applied to the teaching of the short passing skill. This study applied the total sampling method with 25 students of the population. The findings were shown through normality tests using Microsoft Excel; thus, the pre-test average was 17 and posttest was 19.48. From the results of t-test analysis, it showed the tcount is greater than the ttable (10,09 > 2,064). Henceforward, it is concluded that there was an increase in students' short passing skills by using the drilling method.Keywords: Drilling, Short passing, soccer